2018
DOI: 10.3892/ol.2018.8022
|View full text |Cite
|
Sign up to set email alerts
|

Expression of genes and proteins of multidrug resistance in gastric cancer cells treated with resveratrol

Abstract: Abstract. Multidrug resistance (MDR) is a notable problem in the use of chemotherapy. Therefore, studies aimed at identifying substances capable of overcoming resistance of cancer cells are required. Examples of these compounds are polyphenols, including resveratrol, that exert a range of various biological activities. The aim of the present study was to demonstrate the effect of 3,5,4'-trihydroxy-trans-stilbene (resveratrol) on the expression of ATP binding cassette subfamily B member 1, Annexin A1 (ANXA1) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Four hub genes ( TXN, HSPD1, HSPH1 and ATIC ) were related to OS in patients who accepted tamoxifen treatment according to Kaplan–Meier Plotter. It’s indicated that the overexpression of TXN proteins was one of the atypical multidrug resistance mechanisms associated with overexpression of P-glycoprotein ( Mieszala et al, 2018 ). TXN modulate the expression of estrogen responsive genes in breast cancer cells, and reducing oxidized TXN restore tamoxifen sensitivity to previously resistant breast cancer cells ( Rosalind & Deodutta, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Four hub genes ( TXN, HSPD1, HSPH1 and ATIC ) were related to OS in patients who accepted tamoxifen treatment according to Kaplan–Meier Plotter. It’s indicated that the overexpression of TXN proteins was one of the atypical multidrug resistance mechanisms associated with overexpression of P-glycoprotein ( Mieszala et al, 2018 ). TXN modulate the expression of estrogen responsive genes in breast cancer cells, and reducing oxidized TXN restore tamoxifen sensitivity to previously resistant breast cancer cells ( Rosalind & Deodutta, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…In view of these early results in colorectal cancer cells, the combined use of RSV with one of these pharmacological inhibitors of MDR or MRP would counteract the low bioavailability of polyphenol and increase its effectiveness. Moreover, Mieszala et al have recently shown that RSV reduced the expression of ABC subfamily B member 1, annexin A1 (ANXA1) and thioredoxin (TXN) genes and the proteins encoded by these genes which are associated with MDR [33]. These results suggest that RSV could reduce the resistance of cancer cells by affecting the expression of a number of the genes and proteins associated with MDR.…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol has been shown to reverse the resistance to standard classical chemotherapeutics in non-stem cancer and cancer stem cells by sensitizing the cells in multiple ways. It is reported to cause an increased susceptibility to induce cancer cell apoptosis by interfering with pro- and anti-apoptotic factors, by regulating miRNAs, by its effect on drug- and carcinogen-metabolizing enzymes, by interfering with drug resistance gene/protein expressions and respective signaling pathways through poorly understood mechanisms ( Mieszala et al., 2018 ; Zhang et al., 2019 ).…”
Section: Strategies To Eliminate Cancer Stem Cellsmentioning
confidence: 99%